Answer:
(-2, 0)
Step-by-step explanation:
midpoint formula :)
Alex definitely had the most work done between all of them
Answer:
10 million out of 10
Step-by-step explanation:
Answer:
-18
Step-by-step explanation:
let n be the number
(6-n)/3 = 8
6-n = 24
6-24 = n
-18 = n
Answer:
I think its A
Step-by-step explanation:
I factored the polynomial and its factors turned out to be (x-1)(x^2-2x-4), which eliminated the possibilities of 2 and 3. Then i replaced the (-1) in the place of the x and it turned out to be equal to 2, making the first statement true.